Thanks Be to God for Paul J. Wadell: Essays in Honor of a Friend and His Work - Tobias Winright (Journal of Moral Theology, 2021)
This essay introduces readers to a roundtable of five articles honoring Paul Wadell and his work in Catholic moral theology. In it, Wadell's contributions to the field are briefly highlighted, along with how they map onto the landscape of post-Vatican II Catholic moral theology.